Crypto-Minimalism - Davies, Philip R. (Journal of Semitic studies, 2005)
Two recent books by William Dever attempt to ‘correct’ the ‘abuse of archaeology’ by ‘revisionists’ and to establish that archaeology can illuminate the ‘real’ history of ancient Israel. But while caricaturing the work of ‘revisionists’ Dever in fact largely follows their methods and conclusions without acknowledgement. Where he departs from these, he lapses into a naïve version of ‘biblical archaeology’ — which he also criticizes. His attempt to elevate the merits of archaeology and archaeologists over biblical studies and its practitioners also obliges him to ‘revise’ the less than glorious role that archaeologists have played in the last fifty years by resisting major advances in our understanding of ancient Israelite history.